2022
DOI: 10.1186/s12885-022-09947-w
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant FOLFOXIRI prior to chemoradiotherapy for high-risk (“ugly”) locally advanced rectal cancer: study protocol of a single-arm, multicentre, open-label, phase II trial (MEND-IT)

Abstract: Background The presence of mesorectal fascia (MRF) invasion, grade 4 extramural venous invasion (EMVI), tumour deposits (TD) or extensive or bilateral extramesorectal (lateral) lymph nodes (LLN) on MRI has been suggested to identify patients with indisputable, extensive locally advanced rectal cancer (LARC), at high risk of treatment failure. The aim of this study is to evaluate whether or not intensified chemotherapy prior to neoadjuvant chemoradiotherapy improves the complete response (CR) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Although data on toxicity due to pre-operative chemotherapy is lacking in LRRC, RAPIDO trial with LARC patients reported no increase in post-operative complications after 6 cycles of CAPOX [ 7 ]. Moreover, in the current study, the proportion of patients treated with induction chemotherapy in LARC showed an increasing trend (44% vs. 60%, p = 0.129), in part due to MEND-IT trial investigating the benefit of FOLFOXIRI induction chemotherapy in LARC [ 24 ]. Nevertheless, in patients with LARC, no increase in toxicity was observed.…”
Section: Discussionmentioning
confidence: 76%
“…Although data on toxicity due to pre-operative chemotherapy is lacking in LRRC, RAPIDO trial with LARC patients reported no increase in post-operative complications after 6 cycles of CAPOX [ 7 ]. Moreover, in the current study, the proportion of patients treated with induction chemotherapy in LARC showed an increasing trend (44% vs. 60%, p = 0.129), in part due to MEND-IT trial investigating the benefit of FOLFOXIRI induction chemotherapy in LARC [ 24 ]. Nevertheless, in patients with LARC, no increase in toxicity was observed.…”
Section: Discussionmentioning
confidence: 76%
“…LARCs were standardly treated with neoadjuvant (chemo)radiotherapy, whereas LRRC patients underwent neoadjuvant chemoradiotherapy or chemo re-irradiation in the case of previous pelvic irradiation [ 14 ]. Some patients received induction chemotherapy before chemoradiotherapy [ 15 , 16 ]. After neoadjuvant treatment, a bTME was performed.…”
Section: Methodsmentioning
confidence: 99%
“… 67 Chemotherapeutic combinations commonly used are FOLFOX, a combination of 5-FU, leucovorin, and oxaliplatin; FOLFOXIRI, a combination of 5-FU, leucovorin, irinotecan, and oxaliplatin; and FOLFIRI, a combination of 5-FU, leucovorin, and irinotecan. 68 70 …”
Section: Conventional Therapeutic Strategies Against Colon Cancermentioning
confidence: 99%